2006
DOI: 10.1175/jam2421.1
|View full text |Cite
|
Sign up to set email alerts
|

Microphysical and Optical Properties of Atmospheric Ice Crystals at South Pole Station

Abstract: In early February 2001 (during the austral summer), over 900 000 digital images of ice crystals were recorded at the South Pole using two ground-based cloud particle imagers (CPIs). Of these, 721 572 crystals Ͼ50 m were classified into crystal habits. When sorted by number, 30% of the crystals were rosette shaped (mixed-habit rosettes, platelike polycrystals, and rosette shapes with side planes), 45% were diamond dust (columns, thick plates, and plates), and 25% were irregular. When sorted by area, rosette sha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
108
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(116 citation statements)
references
References 36 publications
8
108
0
Order By: Relevance
“…This size appears to delineate the lower limit of ice crystal size responsible (at visible wavelengths) for halo formation according to earlier laboratory studies (Sassen and Liou, 1979;Barkey et al, 2002) and theoretical results (Mishchenko and Macke, 1999). In situ observations at the South Pole station (Shcherbakov et al, 2006a;Lawson et al, 2006) also reported very well-marked 22 • halo peaks with pristine ice crystals no larger than 100 µm. Therefore, the reported ice crystal sizes do not appear to be critical for the halo/no-halo interpretation.…”
Section: Discussionsupporting
confidence: 81%
“…This size appears to delineate the lower limit of ice crystal size responsible (at visible wavelengths) for halo formation according to earlier laboratory studies (Sassen and Liou, 1979;Barkey et al, 2002) and theoretical results (Mishchenko and Macke, 1999). In situ observations at the South Pole station (Shcherbakov et al, 2006a;Lawson et al, 2006) also reported very well-marked 22 • halo peaks with pristine ice crystals no larger than 100 µm. Therefore, the reported ice crystal sizes do not appear to be critical for the halo/no-halo interpretation.…”
Section: Discussionsupporting
confidence: 81%
“…From Walden et al (2003), the atmospheric ice crystals over the Antarctic Plateau in winter is mainly constituted of three major types: diamond dust, blowing snow and snow grains. When sorted by number, Lawson et al (2006) attribute 30 % of the crystals recorded at the Amundsen-Scott South Pole station to rosette shaped (mixed-habit rosettes, plate-like polycrystals and rosette shapes with side planes), 45 % to diamond dust (columns, thick plates and plates) and 25 % to irregular. By mass, the percentages are 57 % rosette shapes, 23 % diamond dust and 20 % irregular.…”
Section: Cloudsmentioning
confidence: 99%
“…The dynamical structure of thunderstorm outflow anvils is of relevance and ha s been discussed extensively (e.g. Lilly, 1988). Its evolution is described as a two-stage process.…”
Section: Tropical Anvil Outflowmentioning
confidence: 99%
“…However, much of the uncertainty in models of storm outflow development and influences on radiative forcing centre on whether the subsequent mixed layer can fully develop before most of the ice within it has precipitated out (Lilly, 1988). Starr and Cox (1985) suggest precipitation is important for the plume development and radiative heating impact, reducing the optical path and hence radiative effect.…”
Section: Tropical Anvil Outflowmentioning
confidence: 99%